Top 50 cited articles on dental stem cell research - Konstantinos Kodonas; Anastasia Fardi; Christos Gogos; Nikolaos Economides (Restorative Dentistry & Endodontics, 2020)
ObjectivesCitation analysis provides a unique insight into how scientific interests and research trends have changed over time. The aim of this study was to report on the 50 top-cited papers in dental stem cell research using the Science Citation Index Expanded provided by the Web of Science database to determine the academic importance of each contribution.Materials and MethodsAfter the screening, article title and type, total citations and citations per year, publication journal, publication year, first and senior authors, country of origin, institution, and university of reprint author were documented for the 50 top-cited articles in dental stem cell research. Keyword analysis was performed to determine which keywords were most/least popular.ResultsTop 50-cited articles were cited between 179 to 2,275 times. The majority of papers were published in 2008 and originated from the United States with the highest contribution from the National Institute of Dental & Craniofacial Research. Journal of Dental Research published the highest number of top-cited articles, followed by Stem Cells and Journal of Endodontics. The greatest number of articles was published by two individual authors, Shi and Gronthos. Among 197 unique keywords, dental pulp stem cells and mesenchymal stem cells were the most frequently used. Thirty-eight of the 50 most cited articles were original articles, and 37 of them were in the field of basic science.ConclusionsBasic science studies in dental stem cell research published in high impact factor journals had the highest citation rates.